Edukasi “Satu Piring Cegah Stunting” sebagai Upaya Preventif bagi Anak dengan Waspada Stunting di Desa Sawaran Lor, Kabupaten Lumajang - Mahfudloh, Filla Apriliani; Qoirunnasikin, Liwa; Kirana, Mutiara Nasywa; Safitri, Puput Linanda; Maghfiroh, Fitrah Ainun; Ardilla, Yunita (J-CEKI : Jurnal Cendekia Ilmiah, 2025)
A condition where a child experiences chronic malnutrition which results in height growth that is not optimal according to age is a symptom of stunting. According to Basic Health Research (Riskesdas) data, the prevalence of stunting in Indonesia is still quite high, reaching 21.5%, while the government targets it to reach 14% by 2024. Efforts are being made to prevent the emergence of symptoms of stunting, especially in Sawaran Lor Village, Lumajang Regency is providing education regarding stunting prevention by utilizing print media in the form of brochures. Taking the theme "One Plate to Prevent Stunting" it is hoped that educational stunting prevention material can be delivered which contains various information such as the meaning and symptoms of stunting, forms of preventing stunting from an early age, portions of nutritious food on one dinner plate, proper parenting patterns, and maintaining a clean environment. This community service aims to identify how to prevent stunting through providing education in Sawaran Lor Village, Lumajang Regency. In this community service, the method used is a qualitative method with a descriptive approach. The location of community service is Sawaran Lor Village, Klakah District, Lumajang Regency. It is hoped that the results of this community service can become recommendations for the local government and related parties in developing more effective policies and programs with the hope that the stunting rate in Sawaran Lor Village can be reduced and children in this village can develop optimally so that they become the nation's successors. who are healthy, independent and productive for the future.